Synthetic Seed Production and Germplasm Conservation of Enicostema axillare (Lam.) raynal ssp. littoralis (Blume) raynal Using Nodal and Root Explants - Loganathan*, Kousalya; Packiaraj Sankaran; Sankarlingam Subbiah; Ragunath Cholairaj (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2022)
In the present study, synthetic seed production of the medicinally important plant Enicostema axillare through nodal and root explants were attempted. Enicostema axillare plantlets were germinated through the production of synthetic seeds using in vitro nodal and root explants. Synthetic seed prepared from 3% Na+ and 100 mm calcium chloride was the optimum concentration for uniform and compact synseed formation. Alginate beads containing in vitro derived nodal explants were successfully entrapped with 3% sodium alginate prepared in half-MS, quarter-MS, full-strength MS, and double-distilled water and 100 mM of CaCl2 solution. Synthetic seeds prepared from full strength MS medium exhibited the highest number of multiple shoots on benzyl amino purine (BAP) 2 mgl-1 and kinetin (KIN) 0.5 mgl-1 in combination with 2 mgl-1 GA3. The capsulated nodal explants germinated and produced multiple shoots of 15.0±1.87 at a high rate (87%) in 2 mgl-1 BAP and KIN 0.5 mgl-1 in combinations with 2 mgl-1 GA3 with a shoot length of 6.24±1.03 cm along with a root number of 28.4±5.50. Synthetic seeds stored at 18ºC were found to be favorable temperature for the preservation of synthetic seeds, and it increased seed germination frequency. The synseed nodal explants prepared using ¼ strength MS medium and stored at 18ºC were preserved for up to 80 days and more without losing germination ability (80%). The fully developed plantlets were hardened on vermiculite (100%) with a survival rate of 71%. This protocol could be used for the conservation of germplasm for long-term storage of E. axillare. Keywords: multiple shoots; synthetic seed; encapsulation; storage; germination; hardening *Corresponding author: E-mail: lkousalya25@gmail.com